2010
DOI: 10.1177/0269215509343848
|View full text |Cite
|
Sign up to set email alerts
|

An original field evaluation test for chronic obstructive pulmonary disease population: the six-minute stepper test

Abstract: This study demonstrated that the six-minute stepper test is a reproducible, sensitive, secure, well-tolerated and feasible test for patients with COPD. The reproducibility and sensitivity of the six-minute stepper test suggests that this test could be used in the evaluation of exercise tolerance in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 35 publications
3
59
1
5
Order By: Relevance
“…They were all low-level patients with significant functional limitations. As most current step tests are 6 minutes in duration [22] [23], which our experience suggests is too strenuous for this patient population to complete, we chose a 2-minute step test for assessment. Our goal was a feasible and highly flexible test for functional assessment with results comparable to a known standard.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They were all low-level patients with significant functional limitations. As most current step tests are 6 minutes in duration [22] [23], which our experience suggests is too strenuous for this patient population to complete, we chose a 2-minute step test for assessment. Our goal was a feasible and highly flexible test for functional assessment with results comparable to a known standard.…”
Section: Discussionmentioning
confidence: 99%
“…Because learning effects with repeated testing have been shown to improve outcomes of the 6MWT [26] as well as step tests [22] we evaluated the effects of familiarity by having subjects perform each test twice. The 5% improvement noted in the 6MWT is consistent with previous reports [5] [10], and the 7% improvement in the 2MST reflects a learning effect that is not significantly different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on field tests for lung capacity measurement is also sparse, although specific lung capacity tests have been performed in laboratory settings on patients with thoracic problems [16][17][18]. In addition, two studies have reported lung capacity field tests carried out in conjunction with population-based physical fitness assessments conducted using the protocols of the China Sports Bureau [19,20].…”
Section: Introductionmentioning
confidence: 99%